Alcohol consumption and Mediterranean Diet adherence among health science students in Spain: the DiSA-UMH Study - Alexander Scholz; Eva Maria Navarrete-Muñoz; Manuela Garcia de la Hera; Daniel Gimenez-Monzo; Sandra Gonzalez-Palacios; Desirée Valera-Gran; Laura Torres-Collado; Jesus Vioque (Elsevier, 2016)
Objective: To describe the association between consumption of different alcoholic beverages and adherence to the Mediterranean diet. Methods: A cross-sectional analysis was conducted of the baseline data of the DiSA-UMH study, an ongoing cohort study with Spanish health science students (n = 1098) aged 17-35 years. Dietary information was collected by a validated 84-item food frequency questionnaire. Participants were grouped into non-drinkers, exclusive beer and/or wine drinkers and drinkers of all types of alcoholic beverages. Mediterranean diet adherence was determined by using a modification of the relative Mediterranean Diet Score (rMED; score range: 0-16) according to consumption of 8 dietary components. We performed multiple linear and multinomial regression analyses. Results: The mean alcohol consumption was 4.3 g/day (SD: 6.1). A total of 19.5%, 18.9% and 61.6% of the participants were non-drinkers, exclusive beer and/or wine drinkers and drinkers of all types of alcoholic beverages, respectively. Participants who consumed beer and/or wine exclusively had higher rMED scores than non-drinkers (β: 0.76, 95%CI: 0.25-1.27). Drinkers of all types of alcoholic beverages had similar rMED scores to non-drinkers. Non-drinkers consumed less fish and more meat, whereas drinkers of all types of alcoholic beverages consumed fewer fruits, vegetables and more meat than exclusive beer and/or wine drinkers. Conclusions: The overall alcohol consumption among the students in our study was low-to-moderate. Exclusive beer and/or wine drinkers differed regarding the Mediterranean diet pattern from non-drinkers and drinkers of all types of alcohol. These results show the need to properly adjust for diet in studies of the effects of alcohol consumption.